1995
DOI: 10.1002/anie.199525041
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Aluminosilicates with Frameworks of Minerals

Abstract: A silanetriol and organoaluminum compounds react smoothly to give aluminosilcates of the type shown, which are soluble in organic solvents. Their cubeshaped Al4Si4O12 groups represent the smallest building blocks of zeolite A. Perhaps compounds of this type will be used in the near future in rational solid‐state syntheses under mild conditions. R1 = (2,6‐iPr2C6H3)(SiMe3)N, R2 = 1,4‐dioxane, THF, alkyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 20 publications
2
35
0
1
Order By: Relevance
“…Similar increases in Si NMR shieldings have been calculated for the formation of single 3-and 4-rings from H 2 Si(OH)2 monomers and have been shown to be in good agreement with experimental data. 19 For unstrained rings (4-rings or larger) the shielding increase appears to be generally about 8-9 ppm for every Si-O-H group converted to Si-O-Si.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Similar increases in Si NMR shieldings have been calculated for the formation of single 3-and 4-rings from H 2 Si(OH)2 monomers and have been shown to be in good agreement with experimental data. 19 For unstrained rings (4-rings or larger) the shielding increase appears to be generally about 8-9 ppm for every Si-O-H group converted to Si-O-Si.…”
supporting
confidence: 76%
“…[1][2][3] Such compounds are interesting for a number of reasons. First, they make it possible to establish whether the principles determinining structural stability are the same in molecular and mineral aluminosilicates.…”
Section: Introductionmentioning
confidence: 99%
“…We have not considered all of the possible isomers of this molecule, but have rather concentrated upon (1) We have also studied some of the possible geometries of the Si 4 Al 4 O 12 H 8 Na 4 and Si 4 Al 4 O 12 H 12 molecules. An alternating isomer of Si 4 Al 4 O 12 H 8 Na 4 with Na + ions near the centers of four faces of the T 8 cube has a calculated geometry very much like that determined by Montero et al 32 (and is found to be more stable than the S 4 symmetry isomer in which the Na + are tetrahedrally disposed). The isomer with four Al-O-Al bonds localized in one of the four-atom rings and with Na + bound to each of these Al-O-Al bridges is less stable by 344 kJ/mol.…”
Section: Resultsmentioning
confidence: 73%
“…The idea that molecular clusters can capture the key chemistry at mineral functional groups is actually quite old. A few visionaries were trying to make this point many years ago, [9,10] but only recently has this idea found a receptive audience. [11][12][13] In this article we review some of research that employs these clusters as guides for interfacial reactions and hydrolytic processes.…”
Section: Introductionmentioning
confidence: 97%